Mediterranean Diet, Psychological Adjustment and Health Perception in University Students: The Mediating Effect of Healthy and Unhealthy Food Groups - Mercedes Vélez-Toral (MDPI AG, 2021)
This study aims to identify the relationships between eating habits and psychological adjustment and health perception, and to analyze potential mediating role of healthy and unhealthy foods in the relationship between adherence to the Mediterranean diet (MedDiet) and the psychological constructs and health perception. The sample was selected through stratified random cluster sampling and was composed of 788 university students. The participants responded to a MedDiet adherence screener and food consumption inventory to assess the eating habits, instruments measuring self-esteem, life satisfaction, curiosity and sense of coherence to assess the psychological adjustment, and single item measuring perceived health. The results revealed 41.9% of the participants had a high consumption of vegetables and 85.1% a low consumption of energy drinks, while 29.9% showed a high adherence to the MedDiet which was positively associated to each psychological variable and healthy foods and negatively with unhealthy foods. In conclusion, a higher adherence to the MedDiet, and the consumption of fruits and vegetables is related to higher psychological adjustment and health perception. However, the relationships between MedDiet and the psychological variables and health perception were fully or partially explained because of the consumption of healthy and unhealthy foods.